Les statues de lions des églises romanes, des gardiens de pierre entre espace profane et espace sacré - Sylvain Chardonnet (Frontière·s)
Statues of lions positioned at the gates are a common component of ancient and medieval shrines and may serve several functions. In the Massif Central territories, many lions with funerary purposes can be found, at first without any direct link with architectural structures. Since antiquity these apotropaic statues have nonetheless been part of a sculpted decor whose codes have been repeated during the Middle Ages. As Romanesque churches reused ancient sculptures, they also copied their design to reaffirm the buildings’ ancestral character. From the 11th to the 13th century, the Marche shire (Limousin) provided the largest number of carved lions in the whole of the Western Europe. Stone lions are placed at the entrance of churches and as such materially delimit the sacred area of the ecclesia from the secular space.